An assessment of indigenous innovations in wet Fufu paste production: prospects, constraints and processing risk implications - Samuela, Lawal Nurudeen; Kolawoleb, Ogedengbe; Smith, Ojo Olukayode Omotayo; Segbenu, Nudamajo Paul (Penerbit Universiti Kebangsaan Malaysia, 2019)
Immense opportunities in cassava-tuber value addition have resulted in the development and application of indigenous innovations by small and medium scale cassava processors across the country. This study examines the prospects and challenges faced by indigenous wet fufu paste processors; highlighting waste generation and handling, processing techniques and inherent processing risks. Data were collected using a structured questionnaire administered in 50 processing clusters scattered across the study area (Ifo, Ogun State, Nigeria). Target oral interviews were used to validate the questionnaire and elicit information on the processing clusters, adopted processing techniques, processing equipment, wastewater generation and disposal techniques, and processing risk factors. Wastewater quality parameters were also obtained to assess the level of compliance with permissible limits and the risk implications of disposed of effluent. Processing operations were entirely manual and dominated by young indigenous women working in organized groups of 2-6 people depending on the expected output. About 47% of the tested wastewater parameters were above local (NESREA - National Environmental Standards and Regulations Enforcement Agency) and international (WHO - World Health Organization) limits. Inorganic constituents like sodium, calcium, magnesium, phosphate and heavy metals were found in low quantities. However, heavy metals (cadmium, lead and chromium) exceed the permissible limits. Open land disposal (50%), nearby streams/rivers (13%) and open drains (37%) are the predominant wastewater disposal technique adopted by processors. The risk implications of these techniques were highlighted, and alternative solutions were proffered to mitigate the identified risks and encourage the development of improved innovations among processors.